ORIGINAL ARTICLE: CAUSE OF STRESS AND COPING MECHANISM AMONG MEDICAL STUDENTS YEAR 2013 – 2015 IN UNIVERSITAS AIRLANGGA - Aulia Rahmi; Azimatul Karimah; Nancy Margarita Rehatta (Jurnal Kedokteran Syiah Kuala, 2019)
Abstract. Background: Stress is response and acknowledged as a natural respond to problems in daily life. Coping is defined as a process used to confront stress with various degree of effectiveness. Purpose: To correlate cause of stress and coping mechanism based on sex and year of admission among Universitas Airlangga medical students year 2013, 2014, and 2015. Method: This study was observational analytic study. Data were taken by self-administrated questionnaires (demographic, Medical Student Stressor Questionnaire, and BriefCOPE)  Result: Respondents were dominated by female (60%) and  out of 90 answers, the most frequent stressor was Academic Relater stressor (45.12%) regardless of the gender and admission year, and the most frequent coping mechanism is Planning (79.50%)  and Religion for female students (80.75%) and 2013 students (78.75%). There was a significant correlation between stressor Intrapersonal and Interpersonal and Teaching and Learning Related also coping mechanism Planning, Humor, and Religion between male and female participants. There was also significant correlation between different admission year for coping mechanism Denial, Humor, and Self Blame. Conclusion: The most common stressor of the student year 2013, 2014, and 2015 with medical major in Universitas Airlangga is Academic Related and the most common coping mechanism is Planning.Keywords: medical student, academic stressor, coping mechanism, observational analytic study